The efficacy of neoadjuvant immunotherapy in gastric cancer, adenocarcinoma of the esophagogastric junction, and esophageal cancer: a meta-analysis - Qian, Mengyi; Fang, Yingying; Xiang, Zhiyi; Zhang, Yueming; Zhan, Hujie; Chen, Xiaotong; Chen, Yihang; Xu, Tinghui (Frontiers in Oncology, 2024)
BackgroundNeoadjuvant immunotherapy holds promise in managing resectable locally advanced gastric cancer (GC), adenocarcinoma of the esophagogastric junction (AEG), and esophageal cancer (EC). However, consensus is lacking regarding the efficacy of programmed death-1 (PD-1) and programmed death ligand 1 (PD-L1) inhibitors in neoadjuvant immunochemotherapy (NICT). This study aims to assess the added benefit of PD-1/PD-L1 inhibitors in neoadjuvant chemotherapy (NCT) for these malignancies.MethodsUp to October 2024, randomized controlled trials, case-control studies, and cohort studies that evaluated the addition of PD-1/PD-L1 inhibitors to NCT were systematically retrieved from electronic databases. The primary endpoints included pathologic complete response (pCR), major pathological response (MPR), overall survival (OS), and progression-free survival (PFS).ResultsThirteen studies published between 2021 and 2024 were analyzed. Statistical analyses revealed significantly higher pCR rates (OR: 2.73, P < 0.001) and MPR rates (OR: 2.99, P < 0.001) in the NICT group compared to NCT group. The PFS was also higher in the NICT group, although the difference did not reach statistical significance (HR: 0.50, P = 0.072).ConclusionThis meta-analysis demonstrates that NICT enhances pathological response rates in patients with resectable locally advanced GC, AEG, and EC. However, no significant long-term prognostic benefits were associated with NICT.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024545725.